US Trade Policy Toward China under Obama, Trump, and Biden Presidencies - Kalinina, Veronika; Fojtíková, Lenka; Hrubý, Michal; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how U.S. trade policy toward China evolved under the Obama, Trump, and Biden administrations and identifies the strategic and economic conditions that shaped the shift from engagement to rivalry. While Obama relied on multilateral institutions, legal dispute mechanisms, and negotiation-oriented initiatives such as the Trans-Pacific Partnership, Trump introduced a confrontational approach centred on tariffs, unilateral pressure, and the explicit framing of China as a strategic competitor. Biden maintained most of Trump’s protectionist and industrial measures while embedding them in a broader technology-focused and alliance-based strategy. To analyse the causal patterns behind this evolution, a crisp-set Qualitative Comparative Analysis (QCA) was conducted across four key policy dimensions: WTO dispute use, protectionism, bilateral negotiations, and industrial strategy. The results show that the combination of protectionist measures and industrial policy is both necessary and sufficient for a rivalry-oriented stance, regardless of differences in diplomatic engagement or multilateral behaviour. These findings suggest that the U.S. shift toward rivalry reflects a deeper structural reorientation driven by technological competition and security concerns rather than short-term political dynamics. The thesis contributes to understanding the logic behind U.S.–China trade relations and offers a systematic comparative perspective on trade policy transformations across administrations.
Vedoucí práce: Lenka Fojtíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses